Construction and Study of Amine Electrodes Based on Membranes Containing Sulfonic Compounds as Active Materials with Different Plasticizers in PVC Matrix Membranes - Na.ssory, N.S.; Musleh, R.M.; Abbas, A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Several  amine  liquid selective  electrodes  were prepared based ontwo  active   materials,   phenol  sulfonic   acid  and   l ,2-dihydroxy-3,5- disulfonic  acid   disodium   salt   with  several   plasticizers,  di-n-butyl phthalate(ORPH),  tri-n-butyl   phosphate   (TBP)   and  a-nitro   phenyl octyl  ether   (NPOE).   Electrode   parameters   were  studied   including, concentration range,  detection  limit,  slope,  life  time,  response  time and  pH  effect.  Excellent   results  were  obtained   based  on  n-hyptylmethyl  amine   with  DBPH  and  phenol  sulfonic   acid  as  an activematerial.  The  slope  was  56.g  mY/decade,  concentration range  was ranged from  1oÂ·' M to 1o-4  M with correlation coefficient  of 0.9999, detection  limit of 6 x l o-) M and pH ranged from 5.6 to less than one.Electrode  based on tri-hutyl amine as a secondary  amine gives a slope48.4 mV/decade   with  good  results  for  the other  parameters, but for dccyl amine  as a  primary  runine give very poor response. Electrodes based  on  secondary   and  tertiat)'  amines  gives  very  poor  response because incompatibility of NOPE  with active  material  and pvc. Also the study  was carried  out for a second  active  material  1,2-dihydroxy-3,5-disulfonic  acid   disodium   salt   and   also   a  good   results   were obtained.